Classification Models for Early Detection of Prostate Cancer. (20th April 2008) - Wichard, Joerg D.; Cammann, Henning; Stephan, Carsten; Tolxdorff, Thomas
Abstract : We investigate the performance of different classification models and their ability to recognize prostate cancer in an early stage. We build ensembles of classification models in order to increase the classification performance. We measure the performance of our models in an extensive cross-validation procedure and compare different classification models. The datasets come from clinical examinations and some of the classification models are already in use to support the urologists in their clinical work.